Risk factors for youth violence: Youth violence commission, International Society For Research On Aggression (ISRA) - Anderson, Craig A. (Aggressive behavior, 2018)
Peer Reviewedhttps://deepblue.lib.umich.edu/bitstream/2027.42/144599/1/ab21766.pdfhttps://deepblue.lib.umich.edu/bitstream/2027.42/144599/2/ab21766_am.pd